2012
DOI: 10.3389/fgene.2012.00132
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of non-coding RNA in neural plasticity, cognitive function, and neuropsychiatric disorders

Abstract: Non-coding RNAs (ncRNAs) have emerged as critical regulators of transcription, epigenetic processes, and gene silencing, which make them ideal candidates for insight into molecular evolution and a better understanding of the molecular pathways of neuropsychiatric disease. Here, we provide an overview of the current state of knowledge regarding various classes of ncRNAs and their role in neural plasticity and cognitive function, and highlight the potential contribution they may make to the development of a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 238 publications
(279 reference statements)
0
46
0
Order By: Relevance
“…Interestingly, some lncRNAs modulate synaptic plasticity and are also linked to cognitive disorders (Spadaro and Bredy, 2012;Qureshi and Mehler, 2011). And some lncRNAs localized near synapses may potentially play a role in MDD (Glanzer et al, 2005;Smalheiser et al, 2008;Lugli et al, 2012;Velleca et al, 1994;Puthanveettil et al, 2013).…”
Section: Lncrnas Related To Synaptic Plasticity Potentially Associatementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some lncRNAs modulate synaptic plasticity and are also linked to cognitive disorders (Spadaro and Bredy, 2012;Qureshi and Mehler, 2011). And some lncRNAs localized near synapses may potentially play a role in MDD (Glanzer et al, 2005;Smalheiser et al, 2008;Lugli et al, 2012;Velleca et al, 1994;Puthanveettil et al, 2013).…”
Section: Lncrnas Related To Synaptic Plasticity Potentially Associatementioning
confidence: 99%
“…Accumulating evidence showed that lncRNAs with a large number and diversity play an important regulator role in brain functions (Guennewig and Cooper, 2014). LncRNAs are highly expressed in the central nervous system, affecting neural stem cell maintenance, neurogenesis and gliogenesis, brain patterning, synaptic and stress responses, neural plasticity and cognitive function (Fenoglio et al, 2013;Fatica and Bozzoni, 2014;Spadaro and Bredy, 2012). For example, lncRNA brain cytoplasmic (BC1) is one of the first lncRNA characterized in the brain, is now known to regulate metabotropic receptor signaling (Centonze et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Brain specimens used in this study were collected postmortem following consent obtained with next of kin, according to tissue banking practices regulated by the Quebec Health Research Fund [32], and based on the OECD Guidelines on Human Biobanks and Genetic Research Databases [33]. Samples were dissected by neuropathology technicians, snap-frozen and stored at -80°C.…”
Section: Douglas Bell-canada Brain Bank Montrealmentioning
confidence: 99%
“…The interaction of ncRNA with epigenetic remodelers is another potential avenue for therapeutic intervention for neurological disorders. In the context of memory maintenance and synaptic plasticity, ncRNA molecules and their processing and regulatory mechanisms are important in maintaining homeostasis of cognitive processes [63]. Importantly, defective ncRNA pathways may lead to neurodegenerative diseases, psychiatric disorders, and brain cancer.…”
Section: Background and Motivationmentioning
confidence: 99%